2014
DOI: 10.1017/s1041610214001628
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of anxiety in centenarians: health, economic factors, and loneliness

Abstract: Results suggest that along with health status (subjective and objective), income inadequacy related to medical expenses and feeling lonely may predispose centenarians to clinically significant anxiety and be important to their overall well-being. Further research is needed on the repercussions of clinical anxiety in centenarians' quality of life and on co-morbid conditions (e.g. depression) at such advanced ages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 28 publications
1
32
1
2
Order By: Relevance
“…While use of anticholinergic medications, risk of falls, higher mortality in residents with cancer, medical specialist consultations, poorer subjective health status, more prescribed medications, impaired vision, and insomnia were also all found to be positively associated with anxiety, information on these factors was limited to one or two studies. These findings are in contrast to those within communitydwelling elderly samples, where poorer self-perceived health (Almeida et al, 2012;Gonçalves et al, 2011;Ribeiro et al, 2015), number of chronic illnesses (Forlani et al, 2014;Gonçalves et al, 2011;Grenier et al, 2011), and cognitive impairment appear to be the three most common biological variables positively associated with anxiety. Given that the number of frail RACF residents experiencing comorbid medical issues is increasing (Dwyer, Stoelwinder, Gabbe, & Lowthian, 2015), and research has found a strong association between depression and both perceived and number of health problems, (Braam et al, 2005; RACF, Residential aged care facility.…”
Section: Discussioncontrasting
confidence: 99%
“…While use of anticholinergic medications, risk of falls, higher mortality in residents with cancer, medical specialist consultations, poorer subjective health status, more prescribed medications, impaired vision, and insomnia were also all found to be positively associated with anxiety, information on these factors was limited to one or two studies. These findings are in contrast to those within communitydwelling elderly samples, where poorer self-perceived health (Almeida et al, 2012;Gonçalves et al, 2011;Ribeiro et al, 2015), number of chronic illnesses (Forlani et al, 2014;Gonçalves et al, 2011;Grenier et al, 2011), and cognitive impairment appear to be the three most common biological variables positively associated with anxiety. Given that the number of frail RACF residents experiencing comorbid medical issues is increasing (Dwyer, Stoelwinder, Gabbe, & Lowthian, 2015), and research has found a strong association between depression and both perceived and number of health problems, (Braam et al, 2005; RACF, Residential aged care facility.…”
Section: Discussioncontrasting
confidence: 99%
“…29 These findings, highlighting the relationship between anxiety and fear of falling, reinforce the importance of screening both conditions as it can improve their detection and treatment. Considering that currently little is known about variables contributing to the presence of anxiety in centenarians, 30 further studies should focus on how fear of falling, as an observable frequent condition, may be influencing the existence of clinically significant anxiety symptoms at such advanced ages.…”
Section: Discussionmentioning
confidence: 99%
“…) that stressed the impact of such variable in subjective health and its role as a strong predictor of psychological distress . A recent study with Portuguese centenarians found that income adequacy related to medical expenses was also an important aspect related to clinical anxiety . Within this scope, income may be a stressing factor for both centenarians and their children.…”
Section: Discussionmentioning
confidence: 99%